Coral Bleaching Phenotypes Associated With Differential Abundances of Nucleocytoplasmic Large DNA Viruses - Messyasz, Adriana; Rosales, Stephanie M.; Mueller, Ryan S.; Sawyer, Teresa; Correa, Adrienne M. S.; Thurber, Andrew R.; Vega Thurber, Rebecca (Frontiers in Marine Science, 2020)
Eukaryotic viruses and bacteriophage have been implicated in disease and bleaching in corals, but the compositional and functional diversity of these viruses in healthy and compromised hosts remains underexplored. To investigate whether viral assemblages differ in concert with coral bleaching, we collected bleached and non-bleached conspecific pairs of corals during a minor bleaching event in 2016 from reefs on the island of Mo’orea, French Polynesia. Using electron microscopy (EM), we identified several viral particle types, all reminiscent of medium to large-sized nucleocytoplasmic large DNA viruses (NCLDV). We also found that viral metagenomes from bleached corals have significantly more eukaryotic virus sequences, whereas bacteriophage sequences are significantly more abundant in viral metagenomes from non-bleached colonies. In this study, we also initiated the assembly of the first eukaryotic dsDNA coral virus genome. Based on our EM imagery and our taxonomic annotations of viral metagenome sequences, we hypothesize that this genome represents a novel, phylogenetically distinct member of the NCLDVs, with its closest sequenced relative being a distant marine flagellate-associated virus. We also showed that this NCLDV is abundant in bleached corals, but it is also present in apparently healthy corals, suggesting it plays a role in the onset and/or severity of coral bleaching.